Risk Factors of Breast Cancer Among Women – A Cross-Sectional Study in Selected Slums of Bhubaneswar City, India - Ganguly, Ria; Patnaik, Lipilekha; Sahu, Trilochan (National Journal of Community Medicine, 2022)
Background: Breast carcinoma is the most commonly diagnosed cancer (27·7%) and the leading cause of death (23·5%) among women in India as per GLOBOCAN 2018. There is considerable evidence that breast cancer risk is related to certain modifiable and nonmodifiable lifestyle factors. Thus, this study was conducted to estimate the prevalence of risk factors of breast cancer in women of age group 18-70 years in selected urban slums. Methodology: This community based cross sectional study was conducted in selected 13 urban slums of Bhubaneswar which comes under the field practice area of Department of Community Medicine, Bhubaneswar, IMS and SUM Hospital Bhubaneswar, Odisha from september 2018 to october 2020. Data were entered to an excel sheet and SPSS software version 20 was used for analysis. Results: Among the total population of 300, the mean age of the study subjects was 42 + 12 years ranging from 20 to 69 years. Married women in the study were 95.3%. Including both modifiable and non-modifiable risk factors, 57% of the participants were having risk factors of breast cancer. Conclusion: Women need to be aware of both modifiable and non-modifiable risk factors for breast cancer to adopt appropriate practices for prevention of Breast cancer.